Research, Creative Activity and Teaching: Overlapping, Synergistic and Effective in Preparing 21st Century Business Professionals - Paul, Ravi (My University, 2011)
RCAW Scholar-Teacher Award
Keywords: RCAW; Research; Teaching; MIS; Education